Mérföldkövek a pedagógussá válás folyamatában: - empirikus kutatás a Nyugat-magyarországi Egyetemen végzett pedagógusok körében - N. Tóth, Ágnes (Magyar Pedagógia, 2014)
This study analyses the experience of engaging in studies in higher education and entering the teaching profession among those who have completed their teacher training at the University of West Hungary. The research distinguishes among different areas of education, such as adult education, special needs education, technical education, kindergarten education, social education, and upper and lower primary education. The DPR database (a system that tracks the careers of university graduates) for our university has been used for the analysis. Based on responses from the research sample (N=731), the article discusses secondary schools, university years, entering the profession and new professional experiences. The paper covers university graduates who practise their chosen educational area and those who obtain their licence to practice but either do not want to or cannot make use of their certificates in the labour market. In summary, responses from ex-students can be useful in more than one way for the further development of our institute or its departments. A number of observations were made. The percentage of men among those with an education degree is lower, and they are attracted to this profession because of their affection towards it and not because of the hope of a secure livelihood. 75% of our students are forced to work while they study, and the ratio of full-time students is high among them. Approximately 50% of those who choose to be teachers come from secondary vocational schools, and only a fraction participated in part-time secondary education. Our student’s choice of university is mainly influenced by the geographical location of the institution and not necessarily by the good reputation of its lecturers. Based on feedback from our ex-students, our priority should be: to further develop our infrastructure (classrooms and student hostels); to enhance our social sensitivity; to advance the quality of practical school trainings; to widen foreign scholarship opportunities; and to provide more assistance to find work after leaving the university. Generally speaking, our students know little about the work of the university leadership. One in three education students was unable to receive his/her degree due to the lack of a language certificate. Nearly half of those attending education trainings do not work in education. 75% of those who work in education found their jobs through personal connections or job advertisements or by personally applying at an employer. None of the respondents found work through career offices at the institute. Respondents were mildly satisfied with the infrastructure of the institute, less satisfied with its human resources and very dissatisfied with foreign scholarship opportunities. Students prefer print materials and materials developed by lecturers to electronic materials. Two thirds of students training to be teachers state that the most popular way of testing their knowledge is working on projects on their own. Half of the respondents prefer traditional oral and written exams to the more modern electronic ones. Generally, our ex-students are mildly satisfied with their jobs, and they can mostly identify themselves with the professional part of it. They are not satisfied with the prestige and the financial rewards of their profession, so nearly 20% of them have additional jobs.